2021
DOI: 10.1017/s0033291721000209
|View full text |Cite
|
Sign up to set email alerts
|

The predictive power of expressed emotion and its components in relapse of schizophrenia: a meta-analysis and meta-regression

Abstract: Background Schizophrenia is a longstanding condition and most patients experience multiple relapse in the course of the condition. High expressed emotion (HEE) has been found to be a predictor of relapse. This meta-analysis and meta-regression examined the association of global EE and relapse specifically focusing on timing of relapse and EE domains. Methods Random-effects model was used to pool the effect estimates. Multiple random-effects meta-regression was used to compute the moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 72 publications
(41 reference statements)
3
31
1
Order By: Relevance
“…The increased critical comments and reduced warmth in the family context further exacerbate the situation. 1 Regarding the caregiver’s relationship with the patient, parents showed lower high EE prevalence rate than partners, friends, and other family caregivers (including sons, daughters, and siblings). Factors affecting high EE experiences are multidimensional, relating among other things to individual and family characteristics, mental status, and psychosocial functioning.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The increased critical comments and reduced warmth in the family context further exacerbate the situation. 1 Regarding the caregiver’s relationship with the patient, parents showed lower high EE prevalence rate than partners, friends, and other family caregivers (including sons, daughters, and siblings). Factors affecting high EE experiences are multidimensional, relating among other things to individual and family characteristics, mental status, and psychosocial functioning.…”
Section: Discussionmentioning
confidence: 96%
“…High expressed emotion (EE) is a known risk factor of relapse in patients with schizophrenia. 1 The classic study by Vaughn and Leff 2 revealed that the 9-month relapse rates of schizophrenia were 53% and 92% for patients experiencing high EE in the family context, among those taking medications and not taking medications respectively, vs a rate below 15% among those patients in low EE family contexts. High EE has 3 components, namely criticism, hostility, and emotional over-involvement (EOI).…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that individuals with schizophrenia are exquisitely sensitive to environmental stress (Nuechterlein and Dawson, 1984;Van Os et al, 2010). Individuals with the disorder whose relatives express high levels of critical comments and/or high levels of self-sacrificing behavior have a significantly greater likelihood of relapse within the subsequent 9 months (Butzlaff et al, 1998;Ma et al, 2021). As the family environment significantly influences prognosis in schizophrenia therefor it served as the impetus for interventions needed to support the patient's recovery and prevent the similar risk of injury in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in relationship may also be linked to reduced carer burden as reported in some MFT studies in a psychosis setting in Hong Kong (4, 5); clients and their families carers are likely in a better place to work on their relationship when there is reduced carer burden. Expressed Emotion (EE) is associated with family burden in families of clients with first episode psychosis (32) and there is evidence to support the use of family-based interventions in reducing EE (33). Besides addressing carer burden, MFT may have the potential to alleviate EE in familial relationships.…”
Section: Processes Of Mftmentioning
confidence: 99%